LIVING QURAN: RESEPSI AL-QUR’AN DI PONDOK PESANTREN AL-HUSNA DESA SIDOREJO PAMOTAN REMBANG - Nur Huda; Athiyyatus Sa’adah Albadriyah (Al-Munqidz : Jurnal Kajian Keislaman, 2020)
This study aims to analyze the al-Qur'an reception at Al-Husna Islamic Boarding School Sidorejo Pamotan Rembang. This research is a qualitative research using inductive descriptive method. Qualitative research is a research procedure that analyzes descriptive data in the form of speech or written observations. Inductive descriptive method aims to describe and analyze data to obtain a general description or description of the al-Qu'ran reception at Al-Husna Islamic Boarding School. This research confirms that the Qur'an is a holy book that is always in harmony with all situations and conditions (ṣāliḥ li kulli zamān wa makān). The theory used by the researcher here is Karl Mannheim's sociological theory of meaning, which focuses on three typologies of meaning, namely objective, expressive, and documentary meanings. This study yielded at least two findings. First, there were several types of receptions at the Al-Husna Islamic Boarding School. Second, the meanings inherent in the reception include, a) objective meaning, that the variety of reception behavior at Al-Husna Islamic Boarding School is part of a symbol of obedience and disbelief towards the pondok regulations, b) the meaning of expression is manifested in the form of self-internalization with values positive values in the continuous learning process of the Koran, and c) documentary meaning is manifested in the form of local contextualization of a comprehensive cultural system.